Treatment Needs and Rates of Mental Health Comorbidity in Adolescent Patients With ARFID - Norris, Mark L.; Obeid, Nicole; Santos, Alexandre; Valois, Darcie D.; Isserlin, Leanna; Feder, Stephen; Spettigue, Wendy (Frontiers in Psychiatry, 2021)
The purpose of this paper is to provide a descriptive overview of a single-center ARFID-specific pilot clinic that sought to better understand the specific needs of patients with ARFID including rates of comorbidities, and to gain insight into treatment requirements. A retrospective cohort study was completed on patients meeting criteria for ARFID admitted to a specialized pilot clinic within a tertiary care hospital. Over an 18 month period, a total of 26 patients were assessed and had follow-up data for a twelve month period. Patients presented with heterogeneous manifestations of ARFID and high rates of comorbid mood and anxiety disorders were noted. Treatment plans were tailored to meet individual needs at assessment and over the treatment period. A multidisciplinary approach was most often administered, including a combination of individual therapy, family therapy, medical monitoring, and prescribed medications. Only 30% of patients were treated exclusively by therapists on the eating disorder team. The experiences gained from this pilot study highlight the need for specialized resources for assessment and treatment of patients with ARFID, the importance of a multidisciplinary approach to treatment, and the necessity of utilization of ARFID-specific measures for program evaluation purposes.